EphrinB/EphB signaling controls embryonic germ layer separation by contact-induced cell detachment. - Nazanin Rohani (Public Library of Science (PLoS), 2011)
Background The primordial organization of the metazoan body is achieved during gastrulation by the establishment of the germ layers. Adhesion differences between ectoderm, mesoderm, and endoderm cells could in principle be sufficient to maintain germ layer integrity and prevent intermixing. However, in organisms as diverse as fly, fish, or amphibian, the ectoderm-mesoderm boundary not only keeps these germ layers separated, but the ectoderm also serves as substratum for mesoderm migration, and the boundary must be compatible with repeated cell attachment and detachment. Principal findings We show that localized detachment resulting from contact-induced signals at the boundary is at the core of ectoderm-mesoderm segregation. Cells alternate between adhesion and detachment, and detachment requires ephrinB/EphB signaling. Multiple ephrinB ligands and EphB receptors are expressed on each side of the boundary, and tissue separation depends on forward signaling across the boundary in both directions, involving partially redundant ligands and receptors and activation of Rac and RhoA. Conclusion This mechanism differs from a simple differential adhesion process of germ layer formation. Instead, it involves localized responses to signals exchanged at the tissue boundary and an attachment/detachment cycle which allows for cell migration across a cellular substratum.